Cooperative Difference in Insolvency Proceedings: Pre-Pack Sales, Fiduciary Duty and the Oppression Remedy - Lund, Anna (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2023)
Mountain Equipment Co-operative used insolvency proceedings under the Companies’ Creditors Arrangement Act to sell its business to a private equity firm. A group of members unsuccessfully challenged the sale in court, raising arguments about the court’s power to approve the sale, the fiduciary obligations of the cooperative’s directors and the oppression remedy. This article suggests that the court would have been justified in granting a remedy to the dissenting members if it had attended to how cooperatives differ from standard corporations. This article highlights salient differences between cooperatives and corporations and then analyzes how these differences were relevant to the court’s analysis of its power to approve the sale, the director’s fiduciary obligations, and the oppression remedy. The sale of Mountain Equipment Co-operative underlines the importance of paying careful attention to a debtor’s legal form in insolvency when the debtor is not a standard corporation.